Why is Multi-Business Forestry Needed to Overcome the Low Performance of Forestry Governance and Food Security in Indonesia? - Suryanto, Suryanto; Nurrochmat, Dodik Ridho; Tarigan, Suria Darma; Siregar, Iskandar Zulkarnaen; Yassir, Ishak; Silalahi, Mangarah; Mansur, Irdika; Harisson, Rhett D.; Wahyudi, Agus; Abdulah, Lutfy (Forest and Society, 2024)
The 0.6% contribution of the forestry sector to GDP is considered very low despite 64.1% of Indonesia's land area being allocated as forests. Most of the 64.8% production forest allocated is not yet optimized for strengthening national food security, in which Indonesia is ranked 65th in the world. Therefore, an innovative forest management system is needed to synergize timber and non-timber production. This paper presents a multi-business forestry (Mb-F) implementation strategy analyzed through a dynamic system-based multi-criterion decision-making tool named Super Model Mb-F (SM Mb-F). SM Mb-F is built based on a causal loop diagram (CLD), which describes the dynamic relationship between land typology suitability and decisions related to the type of business, commodities, land use area, workload, and financing for many variables relating to 5M business principles and sustainability. Results showed that CLD formulated in 280 sub-models in a total of 4,764 decision variables with an error deviation of 6.4%. The SM Mb-F simulation on two sample concession units produces a projected increase in wood supply, employment, and state revenue, plus the provision of new functions such as food, NTFP, and environmental services. These benefits are obtained by business feasibility. Assuming that gradually until 2030, the Mb-F can be implemented in 32% of Indonesia's production forests, then by 2045, it is projected that there will be an increase in wood production by 296.8%, state revenue by 654.3%, and labor absorption by 985.7%, as well as adding food production up to 19.36 M tons. This is because the land use efficiency of the current operation of forest concessions following the Annual Allowable Cut (AAC) under the selective cutting and replanting system in Indonesia (TPTI) is only about 3% of the total area of forest concession. Assuming the cutting cycle is 35 years, timber could be extracted in 1/35 of the total forest concession area. Implementing Mb-F will significantly improve the land use efficiency from about 3% to 90%.  The Mb-F will also restrain the rate of decline in carbon stocks, which is deeper if governance is still under the BAU scenario. This research suggests further global research, emphasizing the importance of innovative models for sustainable forestry governance and food security worldwide.